Health care, human worth and the limits of the particular. Issue 5 (October 1997) - Cherry, C
Abstract : An ethics concerned with health care developments and systems must be historically continuous, especially as it concerns the application to managed structures of key moral-epistemic concepts such as care, love and empathy. These concepts are traditionally most at home in the personal, individual domain. Human beings have non-instrumental worth just because they are human beings and not by virtue of their capacities. Managed health care systems tend to abstract from this worth in respect of both individuals' distinctness and individual identity. The first, a common feature of quantitative approaches to health care assessment and delivery, is avoidable. The second, by contrast, is necessarily sacrificed in impersonally managed structures. Failure to distinguish the two encourages confusion and distress, and the demand for impossible medico-moral relationships.